The Expanding Truffle Environment: A Study of the Microbial Dynamics in the Old Productive Site and the New Tuber magnatum Picco Habitat - Mara Rondolini; Maurizio Zotti; Gilberto Bragato; Leonardo Baciarelli Falini; Lara Reale; Domizia Donnini (Journal of Fungi)
Truffles are valuable underground mushrooms with significant economic importance. In recent years, their cultivation has achieved satisfactory results, but not for all species. The harvesting of white truffles (Tuber magnatum Picco) is still dependent on natural production, which is at risk due to various issues, such as improper forest management. A useful practice to protect natural resources is to promote the expansion of productive forests. In this study, we investigate the dynamics of the microbiome in an old and new truffle forest using an amplicon sequencing approach of the fungal ITS region and the prokaryotic 16S rRNA gene. We monitor the soil biological community’s development to compare differences and similarities between the primary productive forest and the expanding area over a two-year sampling period. In particular, we observed the colonization of vacant ecological niches by certain fungi, such as those belonging to the genus Mortierella. Additionally, we examined the competitive interactions between saprotrophs and ectomycorrhizal fungi (ECM). In both study areas, the bacterial community was dominated by Pseudomonadota, Planctomycetota, and Actinomycetota. The behavior of the Tuber genus differed significantly from other ECMs and displayed positive correlations with bacterial taxa such as Ktedonobacter, Zavarzinella, and Sphingomonas. The present work provides an initial overview of expanding white truffle habitats. Further, more specific research is needed to explore potential connections between individual taxa.